Au Lac De L'Immortalite' ('At the Lake of Immortality'), French... - Auteur inconnu (Wikimedia Commons, 1892)
Notice iconographique issue de Wikimedia Commons. Titre: "Au Lac De L'Immortalite" ('At the Lake of Immortality'), French engraving of the Golden Temple in Amritsar. Illustration for Journal Des Voyages, 3 July 1892. "Au Lac De L'Immortalite" ('At the Lake of Immortality'), French engraving of the Golden Temple in Amritsar. Au Lac De L Immortalite (engraving) by French School, (19th century) | Private Collection | Au Lac De L Immortalite. Illustration for Journal Des Voyages, 3 July 1892.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie